Community Dependence and Participation in Mangrove Management: A Case Study in Kladufu Village, Km 10, East Sorong - Marianus D. Liwun; Roger R. Tabalessy; Melisa Masengi (Lembaga Penelitian dan Pengabdian, Universitas Kristen Papua, 2025)
Mangrove forests on the coast of West Papua hold high ecological and economic values, yet utilization pressure continues to increase. This study aimed to analyze the impacts of mangrove utilization activities on ecosystem conditions and on the socio-economy of the community in Kladufu Village Km 10, East Sorong District, Sorong City. The research was conducted with using a descriptive survey method with semi-structured interviews of 31 purposively selected respondents. Data were analyzed descriptively (quantitative and qualitative). Results showed that most respondents were male (58.1%); of productive age, with low education levels (elementary school 38.7%, junior high school 35.5%); and worked as housewives, stone collectors, mangrove loggers, or fishermen. As many as 67.7% of respondents very frequently utilized mangroves, mainly for firewood and construction materials. Logging frequency was very high (61.3%). Nevertheless, 41.9% of respondents perceived mangrove conditions as better than three years earlier due to replanting activities. Community participation in management was mostly voluntary (71.0%) and motivated by confidence in local knowledge (80.6%). A total of 83.9% desired involvement from the planning stage through to benefit sharing. The utilization impacts on the ecosystem were twofold: improvement in rehabilitated areas versus degradation elsewhere. Impacts on the community were reflected in high economic dependence, alongside strong ecological awareness and social capital. Capacity building and livelihood diversification are needed to achieve mangrove sustainability.